Impact of cardiac resynchronization therapy on mitral valve apparatus geometry and clinical outcomes in patients with secondary mitral regurgitation. Issue 11 (12th September 2017) - Mihos, Christos G.; Yucel, Evin; Capoulade, Romain; Orencole, Mary P.; Upadhyay, Gaurav A.; Santana, Orlando; Singh, Jagmeet P.; Picard, Michael H.
Abstract : Background: Cardiac resynchronization therapy (CRT) may improve secondary mitral regurgitation (MR) in patients with cardiomyopathy. The effects on mitral valve (MV) and left ventricular (LV) geometry, however, have not been clearly defined. Methods: Between 2009 and 2012, 229 CRT implants were performed at a single academic center. Seventy‐one had ≥mild MR at baseline and serial echocardiography, without subsequent MV intervention. The pre‐CRT and follow‐up echocardiograms were retrospectively reviewed for (1) MV and LV geometry measurements; (2) MR grade; and (3) LV remodeling indices. Results: The mean age was 67 ± 15 years, and the cardiomyopathy was ischemic in 37 (52%). At a mean follow‐up of 4.0 ± 1.9 years, there were significant improvements in LV ejection fraction and size, MR grade, MV tenting area and anterior leaflet tethering angle, and end‐systolic interpapillary muscle distance (IPMD), and reductions in moderate‐to‐severe or severe MR (27% vs 15%; P = .04) and New York Heart Association functional class III/IV symptoms (83% vs 41%; P < .001). Multivariable analysis revealed the pre‐CRT MV tenting height (OR 1.25, 95% CI 1.01–1.56; P = .04) and end‐systolic IPMD (OR 1.14, 95% CI 0.99–1.32; P = .08) as independently associated with moderate or greater MR at follow‐up. Finally, at 5 years post‐CRT implantation, the estimated survival and freedom from LV assist device or cardiac transplantation was 61%. Conclusions: CRT results in favorable effects on MV and LV geometry and decreases the prevalence of moderate‐to‐severe or severe MR and heart failure symptoms. The pre‐CRT MV tenting height and IPMD are independently associated with persistent MR at follow‐up.